Management of ganglion by double loop suture technique - Kumar, Pavneesh; Giroti, Chetan; Dhobal, Aviral; Raj Singh, Anoop (Asian Journal of Medical Sciences, 2023)
Background: Ganglion is a common cystic swelling around wrist presenting in outdoor department, clinical examination is sufficient for making diagnosis of simple cyst, cosmesis and pain are main presenting complain. Treatment includes aspiration with or without injections but has high recurrence rate, surgical excision has low recurrence rate but being invasive there are numerous complications and should be warrant depending on patient complain. Minimal invasive loop suture technique has low recurrence and minimal complication. Aims and Objectives: The aim of the study was to manage the ganglion by double loop suture technique. Materials and Methods: One hundred and four patients with volar and dorsal wrist ganglion fulfilling inclusion and exclusion criteria received treatment by minimal invasive loop suture technique, 6-month follow-up was done for reviewing any recurrence of cyst. Results: From these 104 patients, 76 were females and 28 were males, with a median age of 22 years. Ninety-four (90.4%) patients presented with dorsal wrist ganglion and 10 (9.6%) patients had volar wrist ganglion. The size of simple ganglia varied from 10 mm to 32 mm Cosmesis was the most common presenting complaint in 84 patients (80.7%) followed by pain (19.3%). Recurrence of swelling was observed in four patients (3.8%). Complications were encountered in two cases in the form of superficial infection at the site of entry point of threads. Conclusion: Radical surgical excision is gold standard but warranted by patient complains as there are numerous complications. Double loop suture technique is an ambulatory surgical procedure and has very promising results with low recurrence rate and complications.